2021
DOI: 10.1016/j.celrep.2021.109138
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cell-derived endometrial stromal fibroblasts in a cyclic, hormone-responsive, coculture model of human decidua

Abstract: Pluripotent stem cell-derived endometrial stromal fibroblasts in a cyclic, hormone-responsive, coculture model of human decidua Graphical abstract Highlights d Endometrial stromal fibroblasts can be differentiated from human ESCs and iPSCs (PSCs) d PSC-ESFs self-assemble with endometrial epithelial organoids d Cocultured PSC-ESFs and EEOs cyclically respond to hormone treatment and withdrawal d PSC-ESFs respond to epithelial cell signaling while in coculture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Here we report on the development of endometrial assembloids, consisting of gland-like organoids surrounded by a matrix rich in primary EnSC, as novel model to parse the cellular dynamics that govern embryo implantation in cycling human endometrium. While assembloids complement and advance other recently described endometrial organoid models ( Boretto et al, 2017 ; Cheung et al, 2021 ; Fitzgerald et al, 2019 ; Luddi et al, 2020 ; Turco et al, 2017 ), they still lack the cellular complexity of native endometrium, including uNK cells, macrophages, and vascular cells. Nevertheless, we demonstrated that aspects of pathological implantation events can be recapitulated in assembloids, rendering them useful as novel models to study mechanisms of reproductive failure and evaluate potential therapeutic interventions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Here we report on the development of endometrial assembloids, consisting of gland-like organoids surrounded by a matrix rich in primary EnSC, as novel model to parse the cellular dynamics that govern embryo implantation in cycling human endometrium. While assembloids complement and advance other recently described endometrial organoid models ( Boretto et al, 2017 ; Cheung et al, 2021 ; Fitzgerald et al, 2019 ; Luddi et al, 2020 ; Turco et al, 2017 ), they still lack the cellular complexity of native endometrium, including uNK cells, macrophages, and vascular cells. Nevertheless, we demonstrated that aspects of pathological implantation events can be recapitulated in assembloids, rendering them useful as novel models to study mechanisms of reproductive failure and evaluate potential therapeutic interventions.…”
Section: Discussionmentioning
confidence: 94%
“…Based on these insights, we hypothesized that acute senescence is integral to successful implantation by creating conditions for anchorage of the conceptus in an otherwise tightly adherent decidual matrix. To test this hypothesis, we developed an ‘assembloid’ model, consisting of endometrial gland-like organoids and primary EnSC, which recapitulates the complexity in cell states and gene expression of the midluteal implantation window, improving resemblance to endometrial tissue in comparison with existing co-culture models ( Cheung et al, 2021 ; Rawlings, 2021 ). We used this model to establish co-cultures with human blastocysts and demonstrate that aspects of different pathological states associated with implantation failure and miscarriage can be recapitulated in endometrial assembloids by modulating decidual senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Good screens for potential toxicity might help to obviate this problem. Organoid models of the human endometrium have been developed ( Turco et al, 2018 ; Chu Cheung et al, 2021 ), and ultimately co-culture models of iTSC with endometrial organoids would be most useful for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs can be broadly categorised into two categories: pharmacological agents termed "senolytics, " which eliminate senescent cells, and "senomorphics, " which prevent the detrimental cell-extrinsic effects of senescent cells and include SASP inhibitors (63,151). Further, organoid and assembloid technologies now enable rapid screening of the effectiveness of drugs in restoring or enhancing the implantation environment (18,(152)(153)(154). Altogether, a new age of nonhormonal "endometrial therapeutics" appears just around the corner.…”
Section: Summary and Therapeutic Perspectivementioning
confidence: 99%